PENGARUH UANG SAKU TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA SEKOLAH DASAR - Suryatama, Handika Suryatama; Aditya Nugrahanta; Jati Kusuma; Leonardus Rangga Satrio Nugroho (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
Learning progress will only be achieved if the environment is supportive; therefore, parents are expected to act more wisely regarding providing pocket money. This study uses a quantitative approach with a survey research method employing a questionnaire to investigate the relationship between pocket money and mathematics learning outcomes among sixth-grade elementary school students at Karangtengah 2 Elementary School. A total of 17 students participated as the sample in this study. Information was collected through questionnaires and relevant documentation reviews. Data analysis was conducted using descriptive statistical techniques and inferential statistical methods. The R square test analysis yielded a result of 0.0174, indicating that the influence of pocket money on mathematics learning outcomes is 1.74%, while 98.26% is influenced by other variables not examined. Based on these findings, there is a positive, though not significant, relationship between the provision of pocket money and the level of motivation in learning mathematics among students. Additionally, providing pocket money can positively impact the motivation level in learning mathematics among sixth-grade students at Karangtengah 2 Elementary School.